Model of improving the business performance through innovation capability based on transformational leadership - Enita Fatmawati; Nurhidayati Nurhidayati (Review of Management, Accounting, and Business Studies, 2021)
This study aimed to analyze the effect of transformational leadership through innovation capability on business performance studies at Village-Owned Enterprises (Village-Owned Enterprises) in Semarang Regency. Innovation capability is a measure of the achievement of good business performance in Village-Owned Enterprises in Semarang Regency. Respondents in this study were the managers of Village-Owned Enterprises in Semarang Regency. Data were collected through a questionnaire method that was filled out independently by 125 selected respondents where the respondents had managed Village Owned Enterprises in their respective villages in 19 sub-districts in Semarang Regency. The analytical method used is Structural Equation Modeling (SEM) analysis which is run with the SMART-PLS 3.2.9 program. The results of hypothesis testing with SMART-PLS 3.2.9 showed that transformational leadership had a direct effect on innovation capability, transformational leadership had a direct effect on business performance, innovation capability had a direct effect on business performance, and innovation capability was proven to be able to mediate transformational leadership in improving the business performance of Village-Owned Enterprises.